The Implementation of Descente in Hadhanah Disputes: A Juridical and Child Psychological Perspective in Religious Courts - Barkah Ramdhani; Wasman Wasman; Sugianto Sugianto; Edy Setyawan; Khiyaroh Khiyaroh (Universitas Muhammadiyah Bandung, 2026)
This study aims to analyze juridically the implementation of descente (local examination) in influencing judges' consideration of child custody disputes (hadhanah) in the Religious Court by focusing on the psychological perspective of the child. The main problem lies in the limitations of the descente function, which is classically oriented to material matters, but in practice it is beginning to be used to assess the child's parenting and emotional relationships. This study uses a qualitative method with an empirical juridical approach through literature studies, decision analysis, and in-depth interviews with judges. The data were analyzed by examining the suitability of descente practices to Islamic civil procedure law and its relevance to the psychological needs of children, such as a sense of security, emotional closeness, and developmental stages. The results of the study show that descente plays a strategic role in enriching the judge's consideration base because it is able to present the reality of children's lives that are not fully revealed through formal evidence. The child's psychological perspective also emphasizes the urgency of descent as an instrument to actualize the principle of the best interest of the child. However, it was found that there were variations in the intensity, quality, and integration of descent results into the consideration of the decision, which had implications for the inconsistency of the application of child protection principles. Thus, this study recommends strengthening normative guidelines through Supreme Court regulations and increasing the capacity of judges in understanding aspects of child psychology so that the implementation of descente is more optimal as an instrument to protect children's rights and welfare in hadhanah cases.